(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2017)
Even though in the early part of the 20th century, it was generally agreed that science and technology were undeniably superior to religion as a relevant dimension of human experience—perhaps with the goal of marginalizing, privatizing and discrediting it to its extinction—starting in the 1970s, these attitudes have changed. As science started accepting its limitations in explaining the empirical reality, religion became more respectable as a parallel outlook on life. In political terms, during the past four decades, the population from the Global North started manifesting strong attitudes of favorability toward organized religion and spirituality,2 with obvious consequences in the internal and external affairs of the states in which they lived.